A neurophenomenological approach to non-ordinary states of consciousness: hypnosis, meditation, and psychedelics. Issue 2 (February 2023) - Timmermann, Christopher; Bauer, Prisca R.; Gosseries, Olivia; Vanhaudenhuyse, Audrey; Vollenweider, Franz; Laureys, Steven; Singer, Tania; Antonova, Elena; Lutz, Antoine; ,
Abstract: No contemporary unifying framework has been provided for the study of non-ordinary states of consciousness (NSCs) despite increased interest in hypnosis, meditation, and psychedelics. NSCs induce shifts in experiential contents (what appears to the experiencer) and/or structure (how it appears). This can allow the investigation of the plastic and dynamic nature of experience from a multiscale perspective that includes mind, brain, body, and context. We propose a neurophenomenological (NP) approach to the study of NSCs which highlights their role as catalysts of transformation in clinical practice by refining our understanding of the relationships between experiential (subjective) and neural dynamics. We outline the ethical implications of the NP approach for standard conceptions of health and pathology as well as the crucial role of experience-based know-how in NSC-related research and application. Highlights: Non-ordinary states of consciousness (NSCs) induced by hypnosis, meditation, and psychedelics have become increasingly popular in research and clinical practice. However, no contemporary unifying framework has been proposed for their study. A neurophenomenological (NP) approach for the study of NSCs provides a unique opportunity to rigorously investigate content-based and structural aspects of consciousness as dynamic (i.e., process-based), together with their embeddedness at multiple scales comprising brain, mind, body, and context. We illustrate this by providing examples from research using traditional and NP approaches regarding the effects of hypnosis, meditation, and psychedelics on core experiences (e.g., agency, pain, and the sense of self) The NP approach to NSCs stresses the importance of experienced-based know-how for their research and application, and has ethical implications related to the traditional conceptions of health and pathology.